Contribution of Affect and Cognition in Shaping Aesthetic Responses - Stojilovic, Ivan (Primenjena psihologija, 2023)
The human experience of art is unique, being associated with exceptional and transcendent states of consciousness. These experiences are formed based on the interaction between the work of art itself, the observer, and the context. Using the multilevel modelling with crossed random effects analysis, we explored the connection between the affective and cognitive appraisals of a visual work of art and the aesthetic judgment. Two experiments were performed. In the first, lay persons appraised figural paintings with pleasant and unpleasant content. In the second experiment, abstract and realistic paintings were appraised. The results indicate a strong connection between affective appraisal and the aesthetic judgment, especially with the assessment of beauty. Cognitive appraisals are less closely connected to aesthetic appraisals. These results suggest that naive observers use everyday, practical perception when evaluating works of art, and that paintings which evoke "sweet", pleasant, hedonic emotions will be assessed as more aesthetically pleasing. The deviation of a painting from traditional art canons further strengthens the reliance on everyday perception in lay persons. The implications of these results are discussed.